SUDDEN UNEXPLAINED JUVENILE DEATH AND THE ROLE OF MEDICOLEGAL INVESTIGATION: UPDATE ON MOLECULAR AUTOPSY (EuroMediterranean Biomedical Journal, 2026)
In the past few years, contributions of molecular biology assays to the investigation of sudden juvenile death have permitted to clarify some of the pathogenetic aspects of sud- den arrhythmic death, opening the way to preventive action on victims’ relatives.We reviewed literature on the genetics of sudden juvenile death, and on molecular biol- ogy assays performed on autoptic samples.Biological investigation permits the detection of genetic mutations underlying the suscep- tibility to sudden cardiac death of individuals with rare inherited forms of arrhythmia (Long QT Syndrome, Brugada Syndrome, Lev’s disease etc.) through the analysis of criti- cal sequences codifying for ion channel subunits (HERG, KvLQT1, MinK, Mirp1, SCN5A, KCNQ1, KCNH2, KCNE1, KCNE2).The main objective of post-mortem investigation in sudden juvenile death is the detection of treatable monogenic inherited disorders, in order to prevent further deaths among the relatives of the deceased patient.